Developing a Manual for Implementing Group Guidance and Counseling Through Integrated Holistic Program - Hadiarni Hadiarni; Zubaidah Zubaidah; Zulhermindra Zulhermindra (Ta'dib, 2021)
One of the services that should be provided by early childhood education (henceforth PAUD) teachers in the holistic integrative program is group guidance and counseling. Therefore, a manual which can assist them in providing these services is needed. This research aims to develop manual for implementing group guidance and counseling through holistic integrative program. The design of the study was research and development by following the CID development model which consists of 4 stages, namely 1) Define, 2) Design, 3) Develop, and 4) Disseminate. The design was validated by two experts, each of whom was with a professional background in guidance and counseling, and early childhood education respectively. The validation results showed that each aspect of the material, presentation, language and graphics are very valid (82%), valid (76.25), valid (70%) and very valid (85%) respectively. The dissemination stage was conducted through trying out the manual for the implementation of guidance and counseling in PAUD-to-PAUD teachers throughout to get an idea of whether there are still improvements so that the use of this manual can achieve the expected goals